Impact of an antimicrobial stewardship and monitoring of infection control bundle in a surgical intensive care unit of a tertiary-care hospital in India. (March 2021) - Panditrao, Aditi; Shafiq, Nusrat; Kumar-M, Praveen; Sekhon, Amritpal Kaur; Biswal, Manisha; Singh, Gurpreet; Kaur, Kulbeer; Ray, Pallab; Malhotra, Samir; Gautam, Vikas; Gupta, Rajesh; Gupta, Vikas; et al.
Highlights: Routine antimicrobial stewardship activities strengthened by intensive strategies and monitoring of infection control. These favourably benefited metrics for assessing the effectiveness of antimicrobial stewardship interventions. DDD/1000PD and LOT/1000PD showed a decrease following this approach. Use of redundant agents in the form of double cover for Gram-negative organisms and double anaerobic cover was addressed. Timeout/de-escalation, dose optimisation, continued education on rational antimicrobial use, and bundle approach are key. Abstract: Objectives: Antimicrobial stewardship (AMS) in resource-limited settings lacks models that can be readily adapted to their settings. Here we discuss the impact of a combined strategy of AMS and monitoring of infection control practices in a tertiary-care centre of a developing country. Methods: This study was undertaken in the surgical unit of a tertiary-care hospital over an 8-month period. In the first 2 months (baseline phase), prospective audit and feedback alone was undertaken, while in the next 6 months (intervention phase) this was supplemented with strategies such as antimicrobial timeout, correction of doses and bundle approach for prevention of hospital-acquired infections. Results: A total of 337 patients were included (94 in the baseline phase and 243 in the intervention phase). There was a decrease in days of therapy per 1000 patient-days (1000PD) (1112.3 days vs. 1048.6 days), length of therapy per 1000PD (956 days vs. 936.3 days) and defined daily doses (DDD) per 1000PD for most antimicrobials. A decrease in double cover for Gram-negative infections (9.6% vs. 2.9%) but an increase in double anaerobic cover (4.2% vs. 7.4%) was observed. There was a decrease in the incidence of ventilator-associated pneumonia per 1000 ventilator-days in the intervention phase (46.4 vs. 35.4), whereas central line-associated bloodstream infections per 1000 central line-days remained the same (14.7 vs. 14.8). Conclusion: This study shows that implementation of routine AMS activities with monitoring of infection control practices can help decrease overall antimicrobial use. With furtherance of measures to control infection, antimicrobial use may be further curtailed.